2017
DOI: 10.21474/ijar01/5603
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Revascularization (Regeneration) and Mta Apexification for Necrotic Immature Permanent Anterior Teeth With Open Apex: A Randomized Controlled Trial.

Abstract: Introduction: The purpose of the study was to compare the effectiveness of pulp revascularization and MTA apexification in the treatment of necrotic anterior teeth with periapical abscess. Methods: twenty-two patients, each with necrotic immature permanent anterior teeth were randomly divided into 2 groups (Group A apexification and group B regeneration) 11 patient per each group. A triantibiotic paste (metronidazole, ciprofloxacin and doxycycline) was used to disinfect the canal for 21 days. MTA plug was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(19 citation statements)
references
References 22 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…The quality of the included studies was assessed using the JBI critical appraisal tool [16]. Six studies [17][18][19][20][21][22] were included, three were evaluated according to the checklist for randomized controlled trials, and three according to the checklist of cohort studies, as seen in Table 2 and Table 3, respectively. The overall risk of bias among the incorporated studies was assessed.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The quality of the included studies was assessed using the JBI critical appraisal tool [16]. Six studies [17][18][19][20][21][22] were included, three were evaluated according to the checklist for randomized controlled trials, and three according to the checklist of cohort studies, as seen in Table 2 and Table 3, respectively. The overall risk of bias among the incorporated studies was assessed.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The diagnosis and the assessment of each outcome were based on the clinical and radiographic evaluation. A total of 260 non-vital immature permanent teeth were evaluated with follow-up periods ranging from 6 to 24 months [17][18][19][20][21][22]. The review of endodontic treatment used in these studies showed that, initially, all immature teeth were treated by a similar endodontic protocol.…”
Section: Checklistmentioning
confidence: 99%
See 3 more Smart Citations